1983
DOI: 10.1021/ac00264a047
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of size exclusion chromatography columns for molecular weight determination of polyacrylonitrile and poly(vinylpyrrolidone) in N,N-dimethylformamide

Abstract: Calibration curves for poly( acrylonitrile) (PAN) and poly(v1-nyipyrroiidone) (PVP) were constructed by using polyethylene oxide (PEO) as primary standards. Molecular weight of PEO at retentlon volume I , (MA),, was converted to molecular weight of PAN or PVP, (M&, by the equation M, = 8(MA);.Constants 8 and f were calculated by using two polymer samples of PAN or PVP of known molecular weights and the PEO Calibration curve. Constants 8 and t for PAN were 12.76 and 0.866, and those for PVP were 3.15 and 0.959.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…Aggregate structures create early eluting shoulders and prepeaks in SEC chromatograms [17] that are suppressed by the addition of low concentrations, e.g. 0.01 M, of LiBr or LiNO 3 .…”
Section: Sec Optimizationmentioning
confidence: 99%
“…Aggregate structures create early eluting shoulders and prepeaks in SEC chromatograms [17] that are suppressed by the addition of low concentrations, e.g. 0.01 M, of LiBr or LiNO 3 .…”
Section: Sec Optimizationmentioning
confidence: 99%
“…Gel permeation chromatography (GPC) of PAN in N,N-dimethylformamide (DMF) as the eluent significantly overestimates the molecular weight of the PAN in comparison with linear polystyrene standards. 41 Because of this, GPC with a multiangle laser light scattering detector (MALLS-GPC) was used to determine the absolute molecular weights of the PAN. After comparing the results from the two procedures, it was concluded that the measured absolute molecular weights by MALLS were 2.5-2.7 times smaller than those estimated from linear polystyrene standards GPC (M w GPC) (as shown in Table S1 of the Supporting Information).…”
mentioning
confidence: 99%
“…[32][33][34][35] We have shown in recent SEC work using a naphthalene mesophase pitch and a mixture of fullerenes that signal at/near the exclusion limit of the column may be clearly observed in chromatograms of entirely nonpolar samples. 36 Figure 4, c and d, presents SEC chromatograms of the Point of Ayr coal extract and its hydrocracking product 22 with the detector set at 350 and 450 nm, respectively.…”
Section: Resultsmentioning
confidence: 94%